2004
DOI: 10.1051/0004-6361:20031648
|View full text |Cite
|
Sign up to set email alerts
|

Dust enshrouded star-forming activity in Arp 299

Abstract: Abstract. We present mid-infrared spectro-imaging (5−16 µm) observations of the infrared luminous interacting system Arp 299 (= Mrk 171 = IC 694+NGC 3690) obtained with the ISOCAM instrument aboard ISO. Our observations show that nearly 40% of the total emission at 7 and 15 µm is diffuse, originating from the interacting disks of the galaxies. Moreover, they indicate the presence of large amounts of hot dust in the main infrared sources of the system and large extinctions toward the nuclei. While the observed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
39
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 40 publications
13
39
0
Order By: Relevance
“…This conclusion is supported by midinfrared observations such as Gallais et al (2004) in which A V is found to be on order tens rather than hundreds.…”
Section: Comparing Molecular Masses To Dynamical Massessupporting
confidence: 62%
See 1 more Smart Citation
“…This conclusion is supported by midinfrared observations such as Gallais et al (2004) in which A V is found to be on order tens rather than hundreds.…”
Section: Comparing Molecular Masses To Dynamical Massessupporting
confidence: 62%
“…Thus, we are able to choose galaxies with very compact nuclear a Kim et al (1995). b Gallais et al (2004). c Sanders et al (1988).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…ISOCAM's spatial scale was sufficient to map the morphologies of local interacting active systems (see for a review) and agree with results from ground-based high resolution images that (optically-faint or invisible) compact sources located in deeply obscured nuclear regions or interaction interfaces dominate the midinfrared emission (e.g. Soifer et al, 2000;Soifer et al, 2001;Charmandaris et al, 2002;Gallais et al, 2004;Siebenmorgen et al, 2004b). For some sources, diffuse emission between these 'hot-spots' can also contribute significantly to the total mid-infrared emission (e.g.…”
Section: The Importance Of Interactions/mergerssupporting
confidence: 76%
“…the Antennae (Mirabel et al, 1998) Fig. 2; UGC12915,12914 ; NGC 985 (Appleton et al, 2002); Arp 299 (Gallais et al, 2004)). The mid-infrared morphologies depend upon the mass ratio of the progenitor galaxies and the merger stage.…”
Section: The Importance Of Interactions/mergersmentioning
confidence: 99%
See 1 more Smart Citation